Current developments in nanostructurally engineered metal oxide for removal of contaminants in water. Issue 5 (1st March 2023) - Singh, Shreya; Garg, Rahul; Jana, Atanu; Bathula, Chinna; Naik, Soniya; Mittal, Mona
Abstract: Clean water is one of the vital resources of every living being residing on this earth. However, rapid industrialization, growing human population, urbanization, global warming, extensive agricultural practices, and climatic change have deprived them of access to clean water. These factors convert clean water into wastewater by polluting water and making it poisonous due to heavy metals. 3.575 million deaths are observed from diseases caused by waste or polluted water every year, according to the World Health Organization report. Hence, wastewater treatment has become every country's primary concern. Although several conventional methods are available for wastewater treatment, their utilization has been restrained due to the high maintenance cost of equipment, the large surface area for installation, and a large amount of energy. Nanotechnology offers a lot of potential for improving the efficiency of water purification and disinfection. Nanomaterials can remove inorganic and organic pollutants, biological pollutants (fungi, bacteria, and microbes), and heavy metal ions from wastewater. Metal oxide nanoparticles (NPs) are the most diverse class of materials due to their unique properties such as good adsorption capacity, large surface area, improved catalysis, and enhanced reactivity. Hence, metal oxide NPs have applications in wastewater treatment. A comprehensive overview of the numerous metal oxide NPs in wastewater treatment has been presented in this review. Here, in detail, we have discussed zinc oxide, titanium oxide, silver oxide, tungsten oxide, iron oxide, and copper oxide NPs and their application in wastewater treatment. Graphical abstract: Image 1